1. The problem statement, all variables and given/known data Prove the associativity law and the distributive law for convolution: (1) prove F*(G+H)=(F*G)+(F*H) (2) prove: F*(G*H)=(F*G)*H 2. Relevant equations 3. The attempt at a solution (1) proof: using the definition of the laplace using convolution Left hand side: =integral(F(u)(G(t-u)+H(t-u))du =laplace(F)xlaplace(G)+Laplace(F)xlaplace(H) Right hand side: =integral(F(u)G(t-u))du + integral(F(u)H(t-u)du =laplace(F)xlaplace(G)+laplace(F)laplace(H) = left hand side I dont know how to prove the second one. Any help would be v much appreciated.